2009
DOI: 10.1002/hfm.20141
|View full text |Cite
|
Sign up to set email alerts
|

Cultural differences in conceptual models of ride comfort for high‐speed trains

Abstract: This study focuses on an analysis of the difference in cultural experiences for similar services through analyzing the difference in conceptual models of ride comfort for passengers of KTX (Korea Train eXpress) and TGV (Train a Grand Vitesse). These trains operate with identical platforms; KTX was introduced by K-TGV (Korea-TGV) based on TGV (French high-speed train). For the conceptual models of ride comfort, this study surveyed 200 KTX passengers on the Seoul-Busan line (duration: 2 hours 30 minutes) and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…For other industries with high comfort requirements, it also provides a strategy. J. H. Lee et al (2009) found that cultural environment and cultural psychological factors also have an impact on personnel comfort. Gender differences can also have an impact on comfort (Jin et al, 2020).…”
Section: Analysis Of the Comfort Evaluation Modelmentioning
confidence: 99%
“…For other industries with high comfort requirements, it also provides a strategy. J. H. Lee et al (2009) found that cultural environment and cultural psychological factors also have an impact on personnel comfort. Gender differences can also have an impact on comfort (Jin et al, 2020).…”
Section: Analysis Of the Comfort Evaluation Modelmentioning
confidence: 99%
“…), a significant amount of time is also spent in transport microenvironments such as cars, buses, trains, aircraft, and other vehicles. Furthermore, mass transit vehicles, such as buses and trains, are prone to a high risk of epidemic outbreaks and health safety [3], coupled with the risk of thermal discomfort from high solar radiation penetration of vehicle cabins [4], thus necessitating adequate IEQ measures and interventions in developing tropics.…”
Section: Introductionmentioning
confidence: 99%
“…Literature review: Several factors have been identified that impact passenger well-being and comfort in trains including indoor climate parameters like the air and radiant temperatures, air velocity, humidity, and air exchange rate while other aspects such as noise, vibration, barometric variation, light and shadow, colors, and odors are important for achieving passenger comfort during travels [2]. Remarkably, a recent study has evaluated cultural differences in conceptual models of ride comfort in high-speed trains, comparing four viewpoints on the effect of intercultural variables, and classifying critical effects as common (objective effects) and uncommon (subjective effects) [3]. This approach to evaluating ride comfort highlights the peculiarities of occupant behavior that can influence the perception of overall comfort in transport microenvironments considering that culture influences behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In Korea, the first high-speed railway system was introduced in 2004, which was fifth in the world [1,6]. Korea Train eXpress (KTX), the high-speed railway system in Korea, introduced TGV-R, the third generation model of Trainà Grande Vitesse (TGV), the high-speed railway system of France [3,6,7]. KTX includes high-speed trains, which have low carbon emissions and relatively low noise levels and are widely regarded as the next-generation transportation.…”
Section: Introductionmentioning
confidence: 99%